2014
DOI: 10.1513/annalsats.201312-447oc
|View full text |Cite
|
Sign up to set email alerts
|

Does Alcohol Consumption during Multidrug-resistant Tuberculosis Treatment Affect Outcome?. A Population-based Study in Kerala, India

Abstract: Rationale India reports the largest number of multidrug-resistant tuberculosis cases in the world; yet, no longitudinal study has assessed factors related to treatment outcomes under programmatic conditions in the public sector. Objectives To describe demographic, clinical, and risk characteristics associated with treatment outcomes for all patients with multidrug-resistant tuberculosis registered in the Revised National Tuberculosis Control Programme, Kerala State, India from January 1, 2009 to June 30, 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 24 publications
2
41
1
1
Order By: Relevance
“…1 Smoking and alcohol consumption are known to worsen the outcomes in pulmonary tuberculosis. 7,8 However, in our current, we could not see any significant effect of smoking and alcohol consumption. Of note, 9 out of 11 patients who died were alcoholics.…”
Section: Discussioncontrasting
confidence: 81%
“…1 Smoking and alcohol consumption are known to worsen the outcomes in pulmonary tuberculosis. 7,8 However, in our current, we could not see any significant effect of smoking and alcohol consumption. Of note, 9 out of 11 patients who died were alcoholics.…”
Section: Discussioncontrasting
confidence: 81%
“…More recent research revealed a surprising association with infectious diseases such as tuberculosis and HIV/AIDS. [3][4][5] College students are within the high-risk age range to consume alcohol. During these years, many of the them would experience the first encounter with alcohol, and this behavior can be sustained into adulthood.…”
mentioning
confidence: 99%
“…Introduction of a system of TB case notification among the private practitioners in Pune City: Is it operationally feasible?Yes [54]24. Treatment outcomes of MDR-TB patients in Kerala, IndiaYes [55]25. A comparative study on same day sputum smear microscopy with the conventional method in the diagnosis of sputum positive pulmonary TBYes [66]26.…”
Section: Implementation Of Operational Research Training Coursesmentioning
confidence: 99%
“…These included: the status of screening household contacts of sputum smear positive pulmonary TB patients [48,49] and malnourished children attending nutritional rehabilitation centers [50], delays in the initiation of TB treatment after diagnosis [51], whether all TB patients diagnosed in the hospitals attached to medical college were being referred and initiated on treatment under RNTCP [52], reasons for poor uptake of HIV counselling and testing [53], status of notification of TB cases by private health care providers [54], TB treatment outcomes of MDR-TB patients [55], detection of TB cases by mobile medical units [56], innovatively addressing the challenges of routine servicing of binocular microscopes [23] and compliance to infection control practices at health facilities [57]. One study assessed innovative ways of improving programme processes such as use of photo-voice for enhancing patient adherence to therapy [58].…”
Section: Contribution Of or To Policy And Practicementioning
confidence: 99%